Dysfunction of outer segment guanylate cyclase caused by retinal disease related mutations - Zägel, Patrick; Koch, Karl-Wilhelm (Frontiers in Molecular Neuroscience, 2014)
Membrane bound guanylate cyclases are expressed in rod and cone cells of the vertebrate retina and mutations in several domains of rod outer segment guanylate cyclase 1 (ROS-GC1 encoded by the gene GUCY2D) correlate with different forms of retinal degenerations. In the present work we investigated the biochemical consequences of three point mutations, one is located in position P575L in the juxtamembrane domain close to the kinase homology domain and two are located in the cyclase catalytic domain at H1019P and P1069R. These mutations correlate with various retinal diseases like autosomal dominant progressive cone degeneration, e.g. Leber Congenital Amaurosis and a juvenile form of retinitis pigmentosa. Wildtype and mutant forms of ROS-GC1 were heterologously expressed in HEK cells, their cellular distribution was investigated and activity profiles in the presence and absence of guanylate cyclase-activating proteins were measured. The mutant P575L was active under all tested conditions, but it displayed a two-fold shift in the Ca2+-sensitivity, whereas the mutant P1069R remained inactive despite normal expression levels. The mutation H1019P caused the cyclase to become more labile. The different biochemical consequences of these mutations seem to reflect the different clinical symptoms. The mutation P575L induces a dysregulation of the Ca2+-sensitive cyclase activation profile causing a slow progression of the disease by the distortion of the Ca2+-cGMP homeostasis. In contrast, a strong reduction in cGMP synthesis due to an inactive or structurally unstable ROS-GC1 would trigger more severe forms of retinal diseases.